A Simple Model for Turbulent Deposition of Mine Dust - Lijun Xu; Ragula Bhaskar (Society for Mining, Metallurgy & Exploration, 1995)
The transport of dust particles from a turbulent air stream on to the surface of a mine entry is mainly due to the effect of diffusion, sedimentation and inertial impaction. While the literature in aerosol science contains many references on particle deposition, most studies apply to smooth surfaces in small, short tubes. The deposition data from those experiments may not be applicable to deposition in mine airways that have large areas of rough surfaces and extend several thousand meters. This paper describes the mechanisms of mine dust transportation and deposition, specifically, by estimating the turbulent deposition velocity for coal dust in mine airways. Data from in-mine experiments on ambient dust concentration and dust deposition along a straight entry were used. A statistical model for dimensionless turbulent deposition velocity was developed, and compared with the models developed by other researchers. The model shows that the distance from the dust source is an important factor in the turbulent deposition of mine dust.